Epistemological nature of Pedagogy: a quantitative and qualitative re-signification - Loayza Maturrano, Edward Faustino (2014)
This investigation is focused on the relationship between Philosophy of Science and Pedagogy; this article analyzes current problems in society, this scientific approach is important to focus on major research problems. This investigation also suggests a double approach regarding the qualitative-quantitative meta-theoretical analysis of the Pedagogy.